Neuropeptidomic Analysis of a Genetically Defined Cell Type in Mouse Brain and Pituitary. Issue 1 (21st January 2021) - Fricker, Lloyd D.; Tashima, Alexandre K.; Fakira, Amanda K.; Hochgeschwender, Ute; Wetsel, William C.; Devi, Lakshmi A.
Summary: Neuropeptides and peptide hormones are important cell-cell signaling molecules that mediate many physiological processes. Unlike classic neurotransmitters, peptides undergo cell-type-specific post-translational modifications that affect their biological activity. To enable the identification of the peptide repertoire of a genetically defined cell type, we generated mice with a conditional disruption of the gene for carboxypeptidase E ( Cpe ), an essential neuropeptide-processing enzyme. The loss of Cpe leads to accumulation of neuropeptide precursors containing C-terminal basic residues, which serve as tags for affinity purification. The purified peptides are subsequently identified using quantitative peptidomics, thereby revealing the specific forms of neuropeptides in cells with the disrupted Cpe gene. To validate the method, we used mice expressing Cre recombinase under the proopiomelanocortin ( Pomc ) promoter and analyzed hypothalamic and pituitary extracts, detecting peptides derived from proopiomelanocortin (as expected) and also proSAAS in POMC neurons. This technique enables the analyses of specific forms of peptides in any Cre-expressing cell type. Graphical Abstract: Highlights: A method was developed to identify neuropeptides in genetically defined cell types This method does not require physical separation of brain cells The method was validated using mice lacking Cpe expression in Pomc cells PomcCre::CpeFlx mice have low α-MSH but are not obese like global Cpe knockout mice Abstract : We report a method to identify neuropeptides in specific cell types, using mice with a conditional deletion of carboxypeptidase E. It was validated by deleting CPE in proopiomelanocortin cells. Surprisingly, these mice have greatly reduced levels of the anorexigenic peptide α-MSH but are not obese.